Comparison of Salivary pH in patients with Prevalence of Periodontitis with and without type 2 diabetes - Bostan, Sobia; Kiani, Anam Zahid; Khalil Rana, Beenish; Akbar, Tariq; Akhtar, Nouman; Haq, Abdul (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes type 2 and periodontitis has bi-directional relationship not only diabetes is a risk factor for periodontitis but periodontitis could have negative effect on glycemic control. Poor glycemic control is associated with reduced salivary pH. Aim: To compare the difference in salivary PH in patients with Periodontitis with or without Diabetes mellitus (Type 2). Method: A total of 348 consenting subjects were recruited for this investigation. There were 116 with diabetes mellitus and periodontitis, 116 with periodontitis but not diabetes and 116 patients with no periodontitis and diabetes. Salivary PH strips were used to determine the PH levels in each participant and recorded. Results: Participants with periodontitis and diabetes had decreased salivary PH of 6.16 ± 0.03 when compared with individuals with periodontitis who were not diabetic who had PH of 6.62 ± 0.04. The mean salivary PH was compared between the three groups (Control, Periodontitis and DM) where a statistically significant relationship was determined (P<0.05). Conclusion: Our study concluded that the salivary PH of patients with DM and periodontitis is lower than that of the control group. The difference in mean PH value between group 1, group 2 and group3 was statistically significant (P<0.05).